2019
DOI: 10.1111/andr.12597
|View full text |Cite
|
Sign up to set email alerts
|

AMH and INSL3 in testicular and extragonadal pathophysiology: what do we know?

Abstract: Background: It is commonly accepted that testicular function is prevalently regulated by the hypothalamic-pituitary-gonadal axis: The pulsatile secretion of GnRH by the hypothalamus induces pituitary expression of the two gonadotropins FSH and LH, which then stimulate Sertoli and Leydig cells, respectively, therefore regulating steroidogenesis and spermatogenesis. However, a growing body of evidence has recently suggested that other hormones act on the reproductive tract since the early phases of fetal develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 89 publications
2
27
0
3
Order By: Relevance
“…Despite almost nonmeasurable serum levels, intratubular concentrations of AMH are far greater [7,24]. Several studies have reported a progressive decrease of AMH levels during aging [25][26][27], suggesting a progressive decline in Sertoli cell function, which is also fitting with current hypothesis on the negative effects of aging on the male reproductive system [28,29]. As previously mentioned, several authors have investigated the possibility of AMH measurement as a prognostic tool for successful sperm retrieval with testicular sperm extraction techniques (TESE or microTESE): a meta-analysis study conducted by Toulis et al [10] concluded that while the diagnostic value of AMH is not supported, the evidence in these regards is extremely limited.…”
Section: Discussionsupporting
confidence: 67%
“…Despite almost nonmeasurable serum levels, intratubular concentrations of AMH are far greater [7,24]. Several studies have reported a progressive decrease of AMH levels during aging [25][26][27], suggesting a progressive decline in Sertoli cell function, which is also fitting with current hypothesis on the negative effects of aging on the male reproductive system [28,29]. As previously mentioned, several authors have investigated the possibility of AMH measurement as a prognostic tool for successful sperm retrieval with testicular sperm extraction techniques (TESE or microTESE): a meta-analysis study conducted by Toulis et al [10] concluded that while the diagnostic value of AMH is not supported, the evidence in these regards is extremely limited.…”
Section: Discussionsupporting
confidence: 67%
“…During the course of treatment, serum AMH level decreased in both groups, suggesting that both exogenous low-dose T and an increase in endogenous T levels are sufficient to down-regulate AMH secretion in early puberty. As AMH expression is considered to reflect maturation status of Sertoli cells (Sansone et al, 2019), our finding argues against unduly rapid maturation of Sertoli cell population in Lz-treated boys exposed to elevated gonadotrophin levels. Considering that Sertoli cell maturation is intimately related to their replicative capacity, our finding indirectly argues against untoward effect of Lz on future sperm producing capacity.…”
Section: Discussionmentioning
confidence: 54%
“…These symptoms can also be associated with other endocrine parameters: erectile disorders might actually be the clinical manifestations of several conditions affecting other glands or be the result of cardiovascular impairment or damage of nerves as seen in, e.g., type 2 diabetes mellitus [47]. Also muscle weakness has been associated with an impairment in another byproduct of Leydig cells, INSL3 [48,49], as well as with thyroid [50] and adrenal [51] disorders. Several endocrine pathways have been explored in these regards in the EMAS Study, suggesting a complex interplay between the psychological aspects of male sexual behavior, mostly regulated by E2, and the sexual functioning under more direct control from T [52].…”
Section: Discussionmentioning
confidence: 99%